The Odonata of Argentina: state of knowledge and updated checklist - Lozano, Federico (2020)
An updated checklist of the 282 species of Odonata known to occur in Argentina is presented along with distributional information by province and ecoregion. Ten new records for the country and 87 new provincial records are provided. At present, 17 species of Odonata are considered endemic to Argentina, and distribution maps for each of them are provided. Information on larvae and conservation status according to the IUCN Red List of Threatened species is also provided; there are still 98 larvae unknown and 169 species unassessed.